THE IMPACT OF USE OF GADGETS ON SOCIAL DEVELOPMENT OF CLASS VI STUDENTS - Sholihin, Adnan (Journal Of Educational Experts (JEE), 2024)
This study aims to describe the impact of using gadgets on the social development of sixth grade elementary school students. learning carried out in one of the public elementary schools in Sleman Regency. Research uses a qualitative descriptive approach to obtain information in learning activities. Informants in the study were 1 class teacher, 2 maple teachers who taught class VI and one student's guardian. The findings of this study indicate that too frequent use of gadgets will hinder social development and have other negative impacts on elementary school students. The impacts include: 1) The effect of gadgets on students' social interaction, 2) The effect of gadgets on students' speaking and writing skills 3) The effect of gadgets on students' mental health 4) The effect of gadgets on student behavior. The findings and results of the research that has been carried out can be become the basis for follow-up in the efforts to solve the problem. In addition, this research can be a basis and reference for conducting further research and studies in relation to the social development of students